Proactive multi-copy routing protocol for urban vehicular ad hoc network - Hassan, Aslinda; Bahaman, Nazrulazhar (Asian Research Publishing Network (ARPN), 2015)
A vehicular network topology is very dynamic compared to traditional mobile ad hoc network because of the movement and speed of the vehicles. Thus, a vehicular network is always partitioned due to this reason, especially if the vehicle density is low. In this situation where a direct end-to-end path between source and destination can be considered as non-existent, a regular ad hoc routing protocol with complete path discovery mechanism is not feasible since the routing path is usually disconnected due to the intermittent nature of network links. To overcome this problem, vehicles can be used as carriers to deliver messages using store-and-carry forwarding whenever forwarding option via wireless transmission is not available. It has been ascertained by the majority of researches in VANET that the carry and forward procedure can significantly affect an end-to-end delivery delay. This paper focuses on developing a proactive multi-copy routing protocol with carry and forward mechanism that is able to deliver packets from a source vehicle to a destination vehicle at a small delivery delay. The paper emphases on replicating data packets and distribute them to different relays. The proposed protocol creates enough diversity to reach the destination vehicle with a small end-to-end delivery delay while keeping low routing overhead by routing multiple copies independently. The simulation results in an urban grid model show that the proposed multi-copy forwarding protocol is able to deliver packets at small delivery delay compared to a single-copy forwarding algorithm without having to rely on real time traffic data or flooding mechanism